Gallic Acid Entrapped Hydrogel Scaffold For Bone Applications - Panigrahi, Chandan; Ramani, Pratibha; Bargavi, Bargavi (Journal of Neonatal Surgery, 2024)
Introduction: Gallic acid promotes angiogenesis, the formation of new blood vessels, which is crucial for delivering nutrients and oxygen to regenerating tissues. Gallic acid exhibits antimicrobial properties, effectively combating infection during the tissue regeneration process. It can be utilized in wound healing, bone regeneration, cartilage repair, and skin tissue engineering. The presence of gallic acid enhances wound closure, accelerates tissue remodeling, and reduces scar formation, leading to improved wound healing outcomes Materials and Methods: 500 mg of gallic acid is added in 6 % alginate solution, and kept at freeze drying for 12 hours at (-4 deg C) to form a hydrogel membrane. Results: Prepared hydrogel showed antibacterial and antimicrobial properties. Conclusion: The gallic acid-entrapped hydrogel scaffold demonstrates immense potential for tissue regeneration applications. By incorporating gallic acid into the hydrogel matrix, it offers antioxidant, anti-inflammatory, antimicrobial, and angiogenic properties, thereby promoting tissue healing.. Key Words: ; ; ; ; ; ; ; ; ;; ; ; ; ; .